2010
DOI: 10.1038/nature08885
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the elusive supercomplex that drives cyclic electron flow in photosynthesis

Abstract: Photosynthetic light reactions establish electron flow in the chloroplast's thylakoid membranes, leading to the production of the ATP and NADPH that participate in carbon fixation. Two modes of electron flow exist-linear electron flow (LEF) from water to NADP(+) via photosystem (PS) II and PSI in series and cyclic electron flow (CEF) around PSI (ref. 2). Although CEF is essential for satisfying the varying demand for ATP, the exact molecule(s) and operational site are as yet unclear. In the green alga Chlamydo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
360
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 397 publications
(385 citation statements)
references
References 32 publications
14
360
1
Order By: Relevance
“…Moreover, this screen identified four new substrates of STN8: a putative envelope transporter, CP29, the minor antenna of PSII and PGRL1. This protein is involved in cyclic electron flow [51] and is part of a large supercomplex comprising PSI, cyt b 6 f and LHCII in C. reinhardtii [52]. Spectroscopic analysis with stn7, stn8 and the stn7/stn8 double mutant revealed a Stn8-specific effect on the transition between linear and cyclic electron flow [44].…”
Section: Stn8 Kinase and Its Role In Psii Turnover And In The Foldingmentioning
confidence: 99%
“…Moreover, this screen identified four new substrates of STN8: a putative envelope transporter, CP29, the minor antenna of PSII and PGRL1. This protein is involved in cyclic electron flow [51] and is part of a large supercomplex comprising PSI, cyt b 6 f and LHCII in C. reinhardtii [52]. Spectroscopic analysis with stn7, stn8 and the stn7/stn8 double mutant revealed a Stn8-specific effect on the transition between linear and cyclic electron flow [44].…”
Section: Stn8 Kinase and Its Role In Psii Turnover And In The Foldingmentioning
confidence: 99%
“…By equilibrating their light-harvesting capacity, qT leads to a balance between PSII and PSI, which in our simulations restores the redox poise of the PQ pool between states 1 and 2 more extensively than in our experiments. On the other hand, previous studies have suggested that a substantial fraction of LHCII detaches from PSII during the transition to state 2, but does not associate with PSI and remains in a quenched state in the thylakoids [51]. In this case, state transitions are not expected to induce a complete redox balance of the PQ pool, because the decreased activity of PSII is not compensated by a concomitant enhancement of PSI activity.…”
Section: Discussionmentioning
confidence: 89%
“…In Chlamydomonas, the analysis of npq4 stt7 double mutants indicates that qE and qT are functionally linked during high light stress [48]. The qT component has also been linked to the regulation of CEF by the analysis of stt7 mutants [49,50] and the enrichment of CEF supercomplexes in conditions favouring the association of mobile LHCII antennae with PSI [51,52]. However, this conclusion has been recently questioned by a study demonstrating that although the migration of LHCII antennae to PSI can enhance CEF in light-limiting conditions, Chlamydomonas cells may switch from low to high rates of CEF independently of the LHCII kinase Stt7 [53].…”
Section: Introductionmentioning
confidence: 99%
“…[35]). In C. reinhardtii, the formation of a supercomplex including PSI-LHCI and cytochrome b 6 f, which also involves the association of ferredoxin-NADPH oxidoreductase, PGRL1, Ca 2+ sensor protein, and anaerobic response 1 protein, is shown to mediate cyclic electron flow [36][37][38].…”
Section: Introductionmentioning
confidence: 99%